Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1007/s10854-015-3885-3
|View full text |Cite
|
Sign up to set email alerts
|

Doping and thickness variation influence on the structural and sensing properties of NiO film prepared by RF-magnetron sputtering

Abstract: The NiO and NiO-Cu doped films with various Cu contents of 5.68, 10.34, and 14.64 at%. Were deposited on a glass substrate with various thickness 50, 100, and 150 nm by RF-reactive magnetron sputtering technique. The effect of the thickness and the doping on the structural, electrical, and sensory properties of the films was mainly investigated. The X-ray diffraction studies revealed that all the deposited films were of single crystalline nature and exhibited cubic structure with preferential growth along 200 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…49 The carrier density and hole mobility of NiO are 4.30 Â 10 10 cm 3 and 9.67 Â 10 2 cm 2 V À1 s À1 , respectively. 51 The conductivity of NiO is much lower than that of NiS. Therefore, when exposed to H 2 S gas, suldation of NiO to NiS reduced the sensor resistance.…”
Section: Gas Sensing Mechanismmentioning
confidence: 99%
“…49 The carrier density and hole mobility of NiO are 4.30 Â 10 10 cm 3 and 9.67 Â 10 2 cm 2 V À1 s À1 , respectively. 51 The conductivity of NiO is much lower than that of NiS. Therefore, when exposed to H 2 S gas, suldation of NiO to NiS reduced the sensor resistance.…”
Section: Gas Sensing Mechanismmentioning
confidence: 99%
“…Deshwal and Arora [23] studied the sensing response for acetone gas by optimizing the thickness of ZnO thin films and reported a sensing response of 63.3 measured at 320°C for an optimized thickness of 410 nm for a ZnO-sensing layer. Hassan et al [24] deposited 50nm-, 100-nm-, and 150-nm-thin NiO-and NiO-Cudoped films by radiofrequency (RF) magnetron sputtering technique. It was reported that 50-nm-thick NiO-and NiO-Cu-doped thin films gave the highest sensitivity toward NO 2 gas.…”
Section: Introductionmentioning
confidence: 99%
“…Among the nickel oxide family, the simplest compound is NiO. This oxide must fulfill and integrate a wide range of applications as antiferromagnetic layers, p -type transparent conducting films in electrochromic devices, photocatalytic layers, or functional sensor layers for chemical sensors. These different fields are allowed by the combination of its excellent chemical stability and its very interesting electrical, optical and magnetic properties. In addition, NiO thin films have a great potential for their integration and application in industry because it can be easily synthesized as thin coatings by magnetron sputtering. In the case of electrochromic devices, a special attention is paid to the oxidation state of nickel according to the gas mixture. NiO x films show a reversible modulation of its optical properties with respect to the applied voltage.…”
Section: Introductionmentioning
confidence: 99%